NOVOS SABERES, NOVAS PERSPECTIVAS: 10 ANOS DO CURSO DE DOUTORADO EM ENFERMAGEM NA UFBA - Edméia Almeida Cardoso Coelho; Enilda Rosendo do Nascimento; Mirian Santos Paiva (Universidade Federal da Bahia, 2016)
Editorial